2000
DOI: 10.1177/021849230000800322
|View full text |Cite
|
Sign up to set email alerts
|

Hydatid Cyst on Right Ventricular Posterior Wall

Abstract: A 14-year-old boy was investigated for unexplained tachycardia and multiple pulmonary emboli demonstrated by computed tomography. A right ventricular hydatid cyst was diagnosed by echocardiography and successfully excised under cardiopulmonary bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 5 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…[2][3][4][5] Reprint requests to: Y. Ünlü, Atatürk Mah. 2,4,7 Our patient suffered a peripheral embolism, caused by a cyst rupturing into the left ventricle of the heart. 2,4,7 Our patient suffered a peripheral embolism, caused by a cyst rupturing into the left ventricle of the heart.…”
Section: Introductionmentioning
confidence: 91%
“…[2][3][4][5] Reprint requests to: Y. Ünlü, Atatürk Mah. 2,4,7 Our patient suffered a peripheral embolism, caused by a cyst rupturing into the left ventricle of the heart. 2,4,7 Our patient suffered a peripheral embolism, caused by a cyst rupturing into the left ventricle of the heart.…”
Section: Introductionmentioning
confidence: 91%
“…Cardiac hydatid cysts should be treated by surgical excision under CPB since the removal of cyst via this technique is safer. It has been suggested that antihelmintics (mebandazole or albendazole) should be given during the postoperative period because of the risks of vesicular implantation and embolization [8].…”
Section: Discussionmentioning
confidence: 99%
“…4,5,6 A superficial cyst involving only the pericardium or surface of the myocardium can be safely excised without the use of cardiopulmonary bypass with low operative risk as in our case. Other intracardiac locations need cardiopulmonary bypass 5,7,8 . A perioperative cover of steroids has been advised by few to minimize the risk of anaphylactic shock in case there is any accidental spillover of the fluid intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Rarely recurrences have been reported in remote sites due to peripheral or pulmonary embolisations. 4,[5][6][7][8] All patients should receive oral mebendazole or albendazole postoperatively. Albendazole is preferred because of lesser side effects and is given in the dosage of 10-mg/kg-body weight per day for at least 6 months or till clinical improvement is seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation